Treatment options for Achilles tendinopathy: a scoping review of preclinical studies - Nathanael Opoku Agyeman-Prempeh; Huub Maas; George L. Burchell; Neal L. Millar; Maarten H. Moen; Theodoor Henri Smit (PeerJ)
Background Achilles tendinopathy (AT) management can be difficult, given the paucity of effective treatment options and the degenerative nature of the condition. Innovative therapies for Achilles tendinopathy are therefore direly needed. New therapeutic developments predominantly begin with preclinical animal and in vitro studies to understand the effects at the molecular level and to evaluate toxicity. Despite the publication of many preclinical studies, a comprehensive, quality-assessed review of the basic molecular mechanisms in Achilles tendinopathy is lacking. Objectives This scoping review aims to summarize the literature regarding in vitro and in vivo animal studies examining AT treatments and evaluate their effect on tendon properties. Also, a quality assessment of the included animal studies is done. We provide a comprehensive insight into the current state of preclinical AT treatment research which may guide preclinical researchers in future research. Eligibility criteria Treatment options of Achilles tendinopathy in chemically or mechanically induced in vivo or in vitro Achilles tendinopathy models, reporting biomechanical, histological, and/or biochemical outcomes were included. Sources of evidence A systematically conducted scoping review was performed in PubMed, Embase.com, Clarivate Analytics/Web of Science, and the Wiley/Cochrane Library. Studies up to May 4, 2023 were included. Charting Methods Data from the included articles were extracted and categorized inductively in tables by one reviewer. The risk-of-bias quality assessment of the included animal studies is done with Systematic Review Centre for Laboratory Animal Experimentation risk-of-bias tool. Results A total of 98 studies is included, which investigated 65 different treatment options. 80% of studies reported significant improvement in the Achilles tendon characteristics after treatment. The main results were; maximum load and stiffness improvement; fibre structure recovered and less inflammation was observed; collagen I fibrils increased, collagen III fibrils decreased, and fewer inflammatory cells were observed after treatment. However, 65.4% to 92.5% of the studies had an uncertain to high risk of bias according to the risk-of-bias tool of the Systematic Review Centre for Laboratory Animal Experimentation. Conclusions Despite promising preclinical treatment outcomes, translation to clinical practice lags behind. This may be due to the poor face validity of animal models, heterogeneity in Achilles tendinopathy induction, and low quality of the included studies. Preclinical treatments that improved the biomechanical, histological, and biochemical tendon properties may be interesting for clinical trial investigation. Future efforts should focus on developing standardized preclinical Achilles tendinopathy models, improving reporting standards to minimize risk of bias, and facilitating translation to clinical practice.